A Single-Item Measure for Assessing STEM Identity - McDonald, Melissa M.; Zeigler-Hill, Virgil; Vrabel, Jennifer K.; Escobar, Martha (Frontiers in Education, 2019)
Science identity based frameworks have proven fruitful in predicting persistence in careers in Science, Technology, Engineering, and Mathematics (STEM). However, much of the research in this area is qualitative or relies on measures of science identity that have not been validated. Here, we propose and provide initial evidence for the validity and reliability of the single-item STEM Professional Identity Overlap measure (STEM-PIO-1) that aims to assess the broader construct of STEM identity via students’ perceived overlap between the image they have of themselves and the image they have of STEM professionals. Across three studies, we provide evidence of convergent, discriminant, and criterion validity—the measure displays moderate positive associations with adapted measures of STEM identity, explains unique variance relative to related but distinct measures of STEM identity, and is positively associated with STEM attitudes, STEM self-efficacy, mastery goal orientation, and agentic behavior toward one’s graduation goals. The measure differentiates between STEM and non-STEM majors, and is associated with self-reported persistence in one’s STEM major. The single-item measure displays moderate test-retest reliability and an expanded four-item version yields good internal consistency. Although continued validation is needed, the simplicity of the STEM-PIO-1 may prove valuable in its ability to promote consistency in measurement of the STEM identity construct across time, age groups, and disciplines.